Perancangan Komik Digital Wayang Hanoman - Setiyawan, Doni; Henny Lukitasari, Evelyne; Yulianto, Arif (Universitas Sahid Surakarta, 2023)
ABSTRACT The puppet show comic is a typical Indonesian comic whose story is taken from the Indonesian or Indian version of the Mahabharata and Ramayana stories. Most Indonesian people quite well know this story. This design aims to design effective and attractive i llustrations and create digital comics that are conceptualized and adapted to the target reader. The design method used digital comic media so children can read comics through gadgets daily. On the other hand, the work of designing digital comics for wayang hanoman is expected to teach children about the moral messages in the puppet show of hanoman stories, and it can be imitated in their daily habits. Keywords: Comics, Puppet Show of Comics, Digital Comics, Design